LA CULTURA TRIBUTARIA Y LA GESTIÓN MUNICIPAL - Ruiz Vásquez, Juana (2017)
The present study aims to establish the existence of a relationship between the tax culture, operationalized in this case as the arrears in municipal tax payments and the quality of municipal public services management in the district of Lince during the period of 2011 and 2014. To develop the research, a mixed approach (quantitative and qualitative) was used, with a descriptive and correlational scope, non-experimental cross-sectional design, and addressing to the population of citizens enrolled in the municipal taxpayer register of the Lince district, with a probabilistic sample of 298 study subjects. The techniques used were a survey and documentary collection, once the results were obtained they were tabulated, the data was processed with the statistical software of Microsoft Excel. The collection of data and the analysis of the results was empirically verified by the increase in arrears in the payment of taxes, the low level of information on municipal taxes and the poor quality of tax administration of the Lince´s municipal administration perceived in the provision of municipal services of public cleaning, embellishment and public safety.